PENELITIAN TERHADAP PENYEBAB KERUSAKAN JALAN LINGKUNGAN PEMUKIMAN DI KOTA BANJARMASIN - Abdurrahman . (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2019)
The increase in traffic volume causes an increase in traffic density that is not balanced with the capacity of the road will cause problems such as congestion and the occurrence of traffic accidents and road damage that can disrupt the level of performance or service from the road. On residential roads there are different construction specifications because this road includes low-class roads with planned traffic passing through it is not a heavy vehicle because this road is for the needs of residents who want to travel to reach its destination.Because this residential road is made with low specifications, it is prone to damage, this damage can start from the road surface (surface) can also be due to a less stable (labile) road foundation. Generally an ideal road can certainly be passed by all vehicles but not by residential neighborhoods, this road is limited in its ability to accept the burden of passing vehicles because it is classified as a low class, due to several things which can damage the road which include loads , lack of equipment for road equipment, the influence of road or natural environment, in the literature, damage to roads in the form of cracks, subsidence, torn, hollow, longitudinal cracks that develop and do not develop.From the cases encountered in the field it turned out to include the cases included in the literature above, so the researchers with observation and testing in the field found that the consequences of damage to the road were:a.    As a result of very heavy loads it will cause cracks, longitudinal cracks, subsidence and holes.b.    As a result of the environment such as being on the edge of the river it will cause subsidence, long cracks and landslides.c.    As a result of no drainage and submerged it will cause holes, sinks and cracks.d.    As a result of the lack of adhesive material in the form of asphalt it will cause peeling. Keywords: Road, Loads, Damage